2001
DOI: 10.1097/00043764-200110000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Aerobic Exercise Program on Median Nerve Conduction and Symptoms Associated With Carpal Tunnel Syndrome

Abstract: Carpal tunnel syndrome is associated with greater body mass index and less physical activity. To determine the effect of aerobic exercise on median nerve conduction and symptoms suggestive of carpal tunnel syndrome, 30 symptomatic volunteers (30 to 64 years old) with abnormal median nerve conduction studies participated in a 10-month program of supervised aerobic exercise. Changes in percentage of body fat, body mass index, peak oxygen consumption, 14-cm median sensory latency, and hand/wrist symptoms were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Different studies have shown that exercise helps the CTS symptoms subside. Exercise may help hand tendons in the wrist move more easily, preventing swelling or inflammation of tendons in the carpal tunnel (26, 27). In our study, probable CTS was more prevalent in assembly workers than in computer operators.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have shown that exercise helps the CTS symptoms subside. Exercise may help hand tendons in the wrist move more easily, preventing swelling or inflammation of tendons in the carpal tunnel (26, 27). In our study, probable CTS was more prevalent in assembly workers than in computer operators.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is considered the most definitive treatment, with as high as 70–90% of subjects reporting freedom from nocturnal pain after surgery [Katz et al,1998]. Nevertheless, surgery drives up costs and there have been long‐term follow‐up studies suggesting that patients who have undergone carpal tunnel release do no better that those who have been managed with conservative care [Nathan et al,2001]. Conservative treatments vary from injection of corticosteroids to neutral wrist splinting [Wilson and Sevier,2003].…”
Section: Introductionmentioning
confidence: 99%
“…Nathan et al, 2001 studied the effects of long term aerobic exercise on median nerve conduction and symptoms associated with carpal tunnel. They postulated that long term aerobic exercise program improved circulation and oxygen delivery which helps in reducing nerve ischemia (the leading cause of carpal tunnel syndrome) thus improving median nerve conduction velocity 25,28 .…”
Section: Discussionmentioning
confidence: 99%